Strategi Pembelajaran Inkuiri terhadap Motivasi Belajar Siswa pada Mata Pelajaran Akidah Akhlak - Asyifa Muhazira; Iit Sintia; Gusmaneli Gusmaneli (Pusat Riset dan Inovasi Nasional, 2024)
This writing aims to describe the use of inquiry methods in learning moral beliefs. Inquiry learning strategies on students' learning motivation in the subject of moral beliefs. This inquiry-based learning approach is related to creating students to think critically, as well as giving them the opportunity to collect information independently and analyze it. With the opportunity to independently collect information and analyze it.